Midterm postoperative outcomes of different types of surgical reconstruction of sinus venosus atrial septal defects with anomalous pulmonary venous connection: The Results of Prospective Cohort Study - Vishal V. Bhende; Tanishq S. Sharma; Deepakkumar V. Mehta; Bhadra Y. Trivedi; Amit Kumar; Viral B. Patel; Gurpreet Panesar; Kunal Soni; Kartik B. Dhami; Nirja Patel; Sohilkhan R. Pathan; Hardil P. Majmudar (Health Science Reports, 2023)
Abstract Background and Aims Sinus venosus atrial septal defects (SVASDs) constitute a substantial part of atrial septal defects and are usually characterized by anomalous pulmonary venous connection (APVC), causing complications like sinus node dysfunction and arrhythmias. Several surgical approaches are used for treating SVASDs in pediatric patients, including single‐ and two‐patch techniques. The study aimed to prospectively evaluate and compare the safety and efficacy of these two methods with different follow‐up periods. Methods Ten patients aged 1–8 years with SVASDs and partial APVC were enrolled in the study at Bhanubhai and Madhuben Patel Cardiac Centre, Karamsad, India, between December 2018 and October 2021. The single‐patch (sandwich‐patch) technique was used in two patients, whereas the two‐patch (dual‐patch) technique with autologous pericardium was used in seven. Safety was assessed as the absence of complications in the follow‐up periods of 6 months, 1, and 2 years, whereas efficacy was estimated by the preserved sinus rhythm and the development of arrhythmias. Electrocardiographic and echocardiographic methods were used to evaluate both parameters. Results No deaths, reoperations, pulmonary vein, and superior vena cava (SVC) stenosis or phrenic nerve palsy were observed among the 10 patients in the three follow‐up periods. Sinus rhythm was arrested in two of the seven patients who underwent two‐patch repair, whereas no rhythm disturbances occurred in those who underwent single‐patch repair. Conclusion Both techniques used in SVASD repair with autologous pericardium proved to cause the smaller rate of complications in midterm postsurgical phase. However, there is a potentially great risk of the development of sinus node malfunction after the application of the two‐patch technique. Therefore, methods avoiding sinus node interference are preferred in patients with partial APVC involving SVC.